“Tudo começa na internet”? Homossexualidades em contextos interioranos no Rio Grande do Sul - Stack, Daniel da Silva (2022)
This research has as object the construction of masculinity between the users of Grindr in the city of Santa Maria – RS. The digital ethnography is a methodology which aims to understand social phenomenon in digital medias, it being the methodology that has possibilitated to the profiles of the users in Santa Maria, and afterwards, the access to the interlocutors. The young people selected to be a part of this research are students that used to reside in the municipality of Santa Maria in the time of the interviews and are from small municipalities or rural areas from the Rio Grande do Sul state. Investigating the construction of the masculinities to these subjects demanded that the stablished relationship between the context of origin and the city of Santa Maria was understood, which made possible to understand that the origin place of these young people present rigid standards of gender and sexuality, characterized by interlocutors as a conservative and oppressive space. The context of each interlocutor exerted different impact in the construction of their masculinity, the ones that were the closest to the rural area had a stronger presence of countryside signs that defined their masculine behavior. Because they found themselves away from their municipalities of origin and the control regime represented by their family, neighbors and other subjects, these young people could construct their personal presentation and experience their homoerotic desires in a freer manner, but with certain worries related to the visibility of their sexuality. The technological development provided new spaces of sociability, the title of the dissertation expresses that to these subjects the constitution of the homoerotic desire starts on the internet, and it is through these applicatives and social networks that they find their first gay friends and sexual partners. Due to the development of the internet, economic segments started to produce an affective field regulated by market logic. Thus, the applicative interface is marked by the necessity that the users know how to advertise their bodies to be able to constitute relations, which implies that they negotiate with the masculinity standards and body that produce the target subjects of desire.